Measured and modelled sublimation on the tropical Glaciar Artesonraju, Perú - Winkler, M. (2009)
Original abstract: Sublimation plays a decisive role in the surface energy and mass balance of tropical glaciers. During the dry season (May–September) low specific humidity and high surface roughness favour the direct transition from ice to vapour and drastically reduce the energy available for melting. However, field measurements are scarce and little is known about the performance of sublimation parameterisations in glacier mass balance and runoff models. During 15 days in August 2005 sublimation was measured on the tongue of Glaciar Artesonraju (8°58' S, 77°38' W) in the Cordillera Blanca, Perú, using simple lysimeters. Indicating a strong dependence on surface roughness, daily totals of sublimation range from 1–3 kg m-2 for smooth to 2–5 kg m-2 for rough conditions. (The 15-day means at that time of wind speed and specific humidity were 4.3 m s-1 and 3.8 g kg-1, respectively.) Measured sublimation was related to characteristic surface roughness lengths for momentum (zm) and for the scalar quantities of temperature and water vapour (zs), using a process-based mass balance model. Input data were provided by automatic weather stations, situated on the glacier tongue at 4750 m a.s.l. and 4810 m a.s.l., respectively. Under smooth conditions the combination zm=2.0 mm and zs=1.0 mm appeared to be most appropriate, for rough conditions zm=20.0 mm and zs=10.0 mm fitted best. Extending the sublimation record from April 2004 to December 2005 with the process-based model confirms, that sublimation shows a clear seasonality. 60–90% of the energy available for ablation is consumed by sublimation in the dry season, but only 10–15% in the wet season (October–April). The findings are finally used to evaluate the parameterisation of sublimation in the lower-complexity mass balance model ITGG, which has the advantage of requiring precipitation and air temperature as only input data. It turns out that the implementation of mean wind speed is a possible improvement for the representation of sublimation in the ITGG model.